The effects of COVID-19 on sleep and general health of Czech patients with epilepsy - Slonkova, Jana; Chudy, Milos; Togtokhjargal, Ariunjargal; Tomaskova, Hana; Vacovska, Hana; Rytirova, Gisela; Dolezalova, Irena (Heliyon, 2023)
OBJECTIVES: To assess the impact of COVID-19 illness and pandemic era on sleep, general health, health care, and social status in patients with epilepsy in the Czech Republic. METHODS: Our designed and approved questionnaire consisted of 23 questions. We focused on (1) patients' demographic and epidemiological data regarding COVID-19, (2) subjective assessment of sleep; (3) epilepsy, and (4) perception of general health during the first year of the COVID-19 pandemic in the Czech Republic from March 2020 to May 2021. We administered the questionnaires during outpatient visits or by phone calls in three major university Czech epilepsy centers (Ostrava, Brno, Pilsen). RESULTS: We enrolled 227 (100%) patients. The mean age (±SD) was 41.2 ± 14.82 years (min 18, max 86 years), and 138 (61%) were women. COVID-19 was confirmed using the PCR test method in 57 (25.1%) patients. In the pre-pandemic era, 62 (27.3%) patients reported sleep disturbances. Insomnia in 46 (74.2%) and excessive daytime sleepiness in 6 (9.7%) were the most mentioned sleep abnormalities. Nocturnal seizures predispose to sleep impairment (p = 0.014) and vivid dreams and nightmares (p = 0.033). COVID-19 infection significantly increased the risk of vivid dreams and nightmares in patients with diurnal seizures (p = 0.006). Sleep quality impairment and seizure frequency worsening [(p < 0.001) and (p = 0.001), respectively] were the most significant risk factors to perform general health deterioration regardless of having COVID-19 (p = 0.559). The most affected age group was 51+ years (p = 0.033). The three centers provided adequate outpatient care during the first year of the pandemic. The employment and social status of the patients remained unchanged (p = 0.074). CONCLUSIONS: COVID- 19 infection significantly increased the occurrence of vivid dreams and nightmares in patients with diurnal seizures. Sleep quality deterioration and seizure frequency worsening significantly negatively impacted general health performance.